Psychometric properties of the Porto Saudade Scale - Félix Neto (Measurement Instruments for the Social Sciences, 2021)
Abstract Saudade involves psychosocial reactions to several circumstances involving deprivation from loved people and/or familiar locations. This work concerns the development and preliminary validation of an instrument to assess general disposition to saudade, the Porto Saudade Scale (PSS). Three studies were conducted which indicated that the PSS has favorable psychometric properties. Exploratory factor analysis of the PSS demonstrated a single latent saudade factor. The confirmatory factor analysis showed that the single latent model of the PSS is adequate and possesses good internal consistency. As expected, the data also supported the convergent, discriminant, and external validity of the PSS. Saudade was more frequently reported among females than among males. These results suggest the validity of the PSS and emphasize that it is a brief measure with strong psychometric evidence for assessing saudade.